2019
DOI: 10.1021/acs.jpca.9b07823
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical Effects on Platinum Acetylide Two-Photon Chromophores

Abstract: A series of cis-platinum(II) acetylide complexes containing two-photon-absorbing chromophores have been synthesized and characterized to explore the effects of stereochemistry on the nonlinear absorption properties. The molecules feature 4-(phenylethynyl)phenylethynylene (PE2), diphenylaminofluorene (DPAF), and benzothiazolylfluorene (BTF) ligands. The photophysical properties were investigated under one-and two-photon conditions and compared to the known trans analogues via UV−visible absorption, photolumines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 61 publications
2
12
0
Order By: Relevance
“…Since the first report of a convenient synthetic route, platinum acetylide molecules, oligomers, and polymers have been considered as model organometallic complexes in photophysics for fundamental investigation of triplet excited states in π-conjugated materials. In addition, studies have explored potential applications of platinum acetylides in phosphorescent organic-light-emitting diodes (OLED) and solar cells and as nonlinear absorption chromophores. Platinum acetylide materials are air stable, have good thermal stability, and are soluble in common organic solvents, properties which render them processable from solution and by vacuum thermal deposition. One reason for the interest in platinum acetylide materials is fundamental investigation and application of triplet states in organic electronics. ,, Excitation of these complexes is accompanied by rapid singlet → triplet intersystem crossing that affords triplet excitons in high yield. , In some cases, the polymers and complexes exhibit moderate to high room temperature phosphorescence yields.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first report of a convenient synthetic route, platinum acetylide molecules, oligomers, and polymers have been considered as model organometallic complexes in photophysics for fundamental investigation of triplet excited states in π-conjugated materials. In addition, studies have explored potential applications of platinum acetylides in phosphorescent organic-light-emitting diodes (OLED) and solar cells and as nonlinear absorption chromophores. Platinum acetylide materials are air stable, have good thermal stability, and are soluble in common organic solvents, properties which render them processable from solution and by vacuum thermal deposition. One reason for the interest in platinum acetylide materials is fundamental investigation and application of triplet states in organic electronics. ,, Excitation of these complexes is accompanied by rapid singlet → triplet intersystem crossing that affords triplet excitons in high yield. , In some cases, the polymers and complexes exhibit moderate to high room temperature phosphorescence yields.…”
Section: Introductionmentioning
confidence: 99%
“…An excitation wavelength of 600 nm was selected due to the lack of appreciable ground-state absorption (Figure ) coupled with the fact that the triplet excited state absorbs appreciably at this wavelength (Figure ). In addition, previous experiments have shown that the FB and Pt-substituted FB chromophores exhibit pronounced two-photon absorption in the 600–800 nm region. , …”
Section: Resultsmentioning
confidence: 92%
“…In addition, previous experiments have shown that the FB and Ptsubstituted FB chromophores exhibit pronounced two-photon absorption in the 600−800 nm region. 32,38 The z-scan experiment provides qualitative insight into the nonlinear response of a sample by probing the transmittance of optical pulses through the sample at different power density (power per unit area). 61−63 The power density is varied by translating the sample through a focused beam.…”
Section: Scheme 2 Synthesis Of P-fbptmentioning
confidence: 99%
See 2 more Smart Citations